Quality of life of male amateur athletes from Pelotas, Brazil - Cristiano Dall'Agnol; Rodrigo Silva; Fabrício Del Vecchio (Revista Brasileira de Atividade Física e Saúde)
The aims of the present study were to assess and compare the health habits and quality of life (QoL) of amateur athletes in different sports. A total of 88 male amateur athletes, engaged in team (n=33), individual (n=30) and combat sports (n=25) aged between 18 and 35 years participated in the experiment. The subjects underwent individual anamnesis and completed the WHOQOL-bref questionnaire to measure QoL. Information on the frequency and duration of training sessions was also collected. According to the findings, team sport athletes consumed more alcoholic beverages, and those from individual sports obtained higher values in the physical (83.7 ± 9.3 vs 76.8 ± 9.5 points, p = 0.03) and environmental domains (73.4 ± 11.6 vs 66.3 ± 8.9 points, p = 0.03) and overall QoL score (81.2 ± 6.7 vs 75.2 ± 7.9 points, p = 0.01), respectively. No correlations were found between QoL domains and time engaged in the sport (r = 0.01; p = 0.91), number of weekly training sessions (r = 0.09; p = 0.39) and session duration (r = -0.06; p = 0.59). Comparison of QoL results with those of the general population revealed higher levels in the physical and psychological components of amateur athletes. In the present study, engaging in sports was associated with higher QoL levels in amateur athletes, particularly in the physical and psychological domains. Moreover, correlations were found between the overall score and domains of QoL.